2004
DOI: 10.1073/pnas.0401773101
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a thermophilic archaeal virus shows a double-stranded DNA viral capsid type that spans all domains of life

Abstract: Of the three domains of life (Eukarya, Bacteria, and Archaea), the least understood is Archaea and its associated viruses. Many Archaea are extremophiles, with species that are capable of growth at some of the highest temperatures and extremes of pH of all known organisms. Phylogenetic rRNA-encoding DNA analysis places many of the hyperthermophilic Archaea (species with an optimum growth >80°C) at the base of the universal tree of life, suggesting that thermophiles were among the first forms of life on earth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
238
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(242 citation statements)
references
References 30 publications
2
238
0
2
Order By: Relevance
“…The study of viruses in the environment, particularly those infectious to bacteria (bacteriophages) and other prokaryotes, has been driven in recent years by several exciting discoveries (Rice et al 2004;Zhao et al 2013). With the advent of improved genomic techniques for molecular-level analyses, microbiologists are slowly uncovering the depth of viral diversity indigenous to areas other than human physiology.…”
Section: Introductionmentioning
confidence: 99%
“…The study of viruses in the environment, particularly those infectious to bacteria (bacteriophages) and other prokaryotes, has been driven in recent years by several exciting discoveries (Rice et al 2004;Zhao et al 2013). With the advent of improved genomic techniques for molecular-level analyses, microbiologists are slowly uncovering the depth of viral diversity indigenous to areas other than human physiology.…”
Section: Introductionmentioning
confidence: 99%
“…Of the four characterized Rudiviridae, SIRV-1 and SIRV-2 (Prangishvili et al, 1999) were found associated together within their own distinct groups (ARV-1 and SRV are described below). Spherical viruses STIV-1 and STIV-2 (from the proposed 'Turriviridae'; Rice et al, 2004;Happonen et al, 2010) were also found tightly centered within a single group as well. The largest viral group in the seeded network was the SIRV-1 and 2 group, comprising 3.2% of the network contigs (0.15% of reads) and 1.9% of all contigs.…”
Section: Network Viral Groups: What They Representmentioning
confidence: 90%
“…By simply discovering and describing STIV, Rice et al (1) have rendered a service to science. The properties of biological organisms cannot be predicted from first principles, because they are the products of evolution.…”
Section: Reminiscent Of Known Virusesmentioning
confidence: 99%
“…The function of the turrets is not known, but a plausible guess is that they have a role in attaching the virus to the cell and initiating infection. The morphological features are the basis for the authors' name for the virus: STIV, for Sulfolobus turreted icosahedral virus (1).…”
Section: A New Virusmentioning
confidence: 99%
See 1 more Smart Citation